World Experience of Shale Gas Consumption - Витвицький, Я. С.; Лебега, О. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article covers the analysis of resources of shale gas select countries, in which the full estimation of this energy resource has been made. It has been established that, according to various evaluations, theof shale gas resource exceeds that of traditional gas. Main characteristics of shale gas fields have been described in the article. The practices of production of shale gas in the following countries have been analysed: USA - Marcellus, Haynesville, Bamett, Fayetteville,Woodford, Antrim, New Albany; Canada – Monteney, Horn River; China – Fuling; Argentina – Vaca Muerta. The following properties of these main shale formations have been demonstrated: area of distribution of slates, geological reserves, recoverable reserves, gas content, the fraction of free gas, fraction of adsorbed gas, intervals of depth of the shale formations, the average depth of a shale formation, the total thickness of the shale horizon, the effective thickness of the shale, porosity, penetration, organic matter content, clay component contentб flint component content, the degree katagenesis, hydrogen index, the number of drilled wells, the drilling density, productivity of wells. On the basis of the analysis the criteria for determining the most promising zones for possible commercial shale gas production from shale formations of other oil and gas production regions have been determined.